Bibliometric Computational Mapping Analysis of Learning Video in Beauty Field (Vocational High School & University) Using VosViewer - Chairani, Vici Syahril (The Indonesian Journal of Computer Science, 2023)
This study aims to analyze the use of learning videos in Beauty Vocational Schools and Beauty study programs at the University level between 2013 and 2023 using bibliometric computational mapping analysis methods. Publish or Perish (PoP) software was used to collect publication data from the Google Scholar database using the keywords "Video Tutorial" AND "SMK" AND "Beauty". The search through Publish or Perish resulted in 285 articles. After elimination and rechecking, 78 articles were analyzed using VosViewer. The analysis results show that the number of publications related to this topic between 2013-2023 is still small, the highest number of publications occurred in the year "2022" with a total of "28" articles, while the lowest was in the year "2013-2015", where each year only "1" article was published. Keyword co-occurrence analysis using VOSViewer resulted in 12 terms grouped into 5 clusters. Network and density visualization showed several keywords that frequently appeared, namely video tutorials, video tutorial media and learning media. In addition, the overlay visualization illustrates keywords that have been trending in recent years namely video, video tutorial, learning video and learning media. Based on data analysis, it can be concluded that research related to the creation and utilization of video tutorials in learning in the field of beauty is still very little and not varied. There are still many subjects in Beauty Vocational Schools or courses in Beauty study programs that do not have video tutorials. This is an opportunity for academics and researchers in the field of Beauty.